Quantifying watershed‐scale groundwater loading and in‐stream fate of nitrate using high‐frequency water quality data. Issue 1 (17th January 2016) - Miller, Matthew P.; Tesoriero, Anthony J.; Capel, Paul D.; Pellerin, Brian A.; Hyer, Kenneth E.; Burns, Douglas A.
Abstract: We describe a new approach that couples hydrograph separation with high‐frequency nitrate data to quantify time‐variable groundwater and runoff loading of nitrate to streams, and the net in‐stream fate of nitrate at the watershed scale. The approach was applied at three sites spanning gradients in watershed size and land use in the Chesapeake Bay watershed. Results indicate that 58–73% of the annual nitrate load to the streams was groundwater‐discharged nitrate. Average annual first‐order nitrate loss rate constants (k) were similar to those reported in both modeling and in‐stream process‐based studies, and were greater at the small streams (0.06 and 0.22 day −1 ) than at the large river (0.05 day −1 ), but 11% of the annual loads were retained/lost in the small streams, compared with 23% in the large river. Larger streambed area to water volume ratios in small streams results in greater loss rates, but shorter residence times in small streams result in a smaller fraction of nitrate loads being removed than in larger streams. A seasonal evaluation of k values suggests that nitrate was retained/lost at varying rates during the growing season. Consistent with previous studies, streamflow and nitrate concentrations were inversely related to k. This new approach for interpreting high‐frequency nitrate data and the associated findings furthers our ability to understand, predict, and mitigate nitrate impacts on streams and receiving waters by providing insights into temporal nitrate dynamics that would be difficult to obtain using traditional field‐based studies. Key Points: Daily groundwater and runoff N loads and in‐stream retention are quantified from nitrate sensor data Groundwater contributes greater than half of the annual N load to the streams Ten to twenty‐five percent of the annual N load is retained by the in‐stream environment